SI DOEL (Donat Tiwoel): Inovasi Pengenalan dan Pengembangan Tiwul Sebagai Makanan Pokok Khas Yogyakarta - Atmaja, Althea Farina; Priyawan, Adha; Fardani, Nadya; Zaqina, Radinda Bian; Kusumaningrum, Mita; Petrus, Himawan Tri Bayu Murti (Program Kreativitas Mahasiswa - Kewirausahaan, 2014)
The doel (Doenat Tiwoel) is a Tiwul processed products innovation in the form of donuts with different flavors at a price of Rp2000.00. Tiwul was chosen as the raw material because it has a higher carbohydrate content than rice, and safe for people with diabetes (Verawati and friends, 2011). Unfortunately Tiwul still not well liked by the society, where Tiwul is currently hard to find. Therefore, the Doel will introduce back Tiwul to the society. Si Doel production process consists of three phases: preparation, sales, and evaluation of the certification. The Doel products is packaged in plastic wrap and also attached a gold laced and a paper filled with the brand, Tiwul facts, and the number of calories in order to attract Doel and can educate consumers. The distribution of Doel is small shops, campus cafeteria, and special ordering from students and public consumers.This business will continue, for proof, in August , Doel has made an agreement with the owner of food carts and food shops. Keywords : Donut, Tiwul, Packaging, Distribution